2005
DOI: 10.1096/fj.04-3580com
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of thePEMTgene and susceptibility to nonalcoholic fatty liver disease (NAFLD)

Abstract: Phosphatidylethanolamine N-methyltransferase (PEMT) catalyzes phosphatidylcholine synthesis. PEMT knockout mice have fatty livers, and it is possible that, in humans, nonalcoholic fatty liver disease (NAFLD) might be associated with PEMT gene polymorphisms. DNA samples from 59 humans without fatty liver and from 28 humans with NAFLD were genotyped for a single nucleotide polymorphism in exon 8 of PEMT which leads to a V175M substitution. V175M is a loss of function mutation, as determined by transiently transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
178
3
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(190 citation statements)
references
References 42 publications
7
178
3
2
Order By: Relevance
“…Supplemental Material can be found at: ( 26 ). Interestingly, a polymorphism of the human PEMT gene is associated with diminished activity and may confer susceptibility to nonalcoholic fatty liver disease (NAFLD) ( 27,28 ). NAFLD shares common clinical manifestations with MetS, such as abdominal obesity, T2D, dyslipidemia, and insulin resistance ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Supplemental Material can be found at: ( 26 ). Interestingly, a polymorphism of the human PEMT gene is associated with diminished activity and may confer susceptibility to nonalcoholic fatty liver disease (NAFLD) ( 27,28 ). NAFLD shares common clinical manifestations with MetS, such as abdominal obesity, T2D, dyslipidemia, and insulin resistance ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…In apparent contrast, no association was found between the V175M polymorphism and steatosis in the Dallas Heart Study (62). The patients examined in the Dallas Heart Study included multiple races (63), whereas in the study by Song et al (60), most subjects were Caucasian. When only Caucasian subjects were compared, there was a similar relationship between the V175M polymorphism and liver disease (63).…”
Section: Pemt and Gene Expressionmentioning
confidence: 90%
“…A polymorphism in the human PEMT gene is associated with nonalcoholic fatty liver disease (60). Controls and patients with liver disease were evaluated for a Val-to-Met substitution at residue 175 of the PEMT human protein.…”
Section: Pemt and Gene Expressionmentioning
confidence: 99%
“…A small study of reported that the frequency of the PEMT variant V175M was higher in 28 biopsy-confi rmed NAFLD patients (0.81) compared with control subjects with normal hepatic triglyceride content (0.61) ( 193 ). In addition, in vitro transfection experiments in McArdle-RH7777 cells showed that V175M had diminished activity compared with wild-type PEMT ( 193 ).…”
Section: Pemtmentioning
confidence: 99%